Reliability and Validity of the Turkish Version of Children's Somatization Inventory - ERGÜN, AYŞE; ŞİŞMAN, FATMA NEVİN; KADIOĞLU, HASİBE (ELSEVIER SCIENCE INC, 2012)
Purpose: The purpose of this study was to examine the psychometric properties of the Children's Somatization Inventory (CSI) in Turkish schoolchildren and adolescents. Methods: The CSI was translated using translation and back-translation. The participants were 813 schoolchildren, adolescents and their parents (n = 453). Content and construct validity were assessed to test the validity of the CSI-24. Internal consistency reliability, interrater reliability (child-parent agreement) and test-retest reliability were assessed to test the reliability of the CSI-24. Results: Psychometric analyses of the Turkish version of the CSI-24 indicate high reliability and good content and construct validity. Conclusion: The Turkish version of the CSI-24 is a useful instrument for measuring self-reported somatic complaints in Turkish schoolchildren and adolescents between the ages of 9 and 15. Copyright (C) 2012, Korean Society of Nursing Science. Published by Elsevier. All rights reserved.
Keywords: child; psychology; reliability and validity; somatization disorder; SOMATIC COMPLAINTS; PSYCHOMETRIC PROPERTIES; ABDOMINAL-PAIN; ADOLESCENTS; SYMPTOMS